Influence of the infusion of beetroot seeds (Beta vulgaris) on the indices of protein and carbohydrate exchange in animals in the sub-chronic and chronic experiment after exposure to copper acetate - Konkabaeva, A.E.; Sirman, D.Yu.; Tykezhanova, G.M.; Baranova, T.N.; Kolossov, R.A. (KSU publ., 2018)
In article is presented the results of studies of protein and carbohydrate metabolism in experimental animals under the influence of copper acetate in the tolerable daily intake (TDI) doses. Positive effects of correction with the infusion of Beta vulgaris seeds were studied. It is shown that the consumption of copper acetate by the animals at the level of TDI has a negative effect on the basic biochemical parameters of protein and carbohydrate metabolism. As a result of the study, it was found that the main indicators of blood biochemistry are directly depended on the duration of the effect of copper on the body of experimental animals. Receiving a solution from the infusion of Beta vulgaris’s seeds as a correction in the presence of copper acetate caused a positive effect, which is manifested by a decrease in the synthesis of metabolic wastes (urea and creatinine). Сopper acetate after correcting of infusion of seeds activated the processes of protein synthesis and glycolysis. Apparently, the intake of copper acetate, causing toxic effects, is simultaneously a stress factor that caused a significant release of glucose into the blood, which is the manifestation of the acute phase of the stress response in the first group. A prolonged exposure to copper acetate led to depletion of energy reserves and a decrease in the deposition of glucose in the liver, which is manifested by a significant decrease in plasma glucose levels in experimental animals after 4 months of the experiment.
Мыс ацетатының əсері кезінде кəдімгі қызылша тұқымы (Beta vulgaris) тұнбасының жедел жəне созылмалы тəжірибедегі жануарлардың ақуыз жəне көмірсу алмасуының көрсеткіштеріне əсері
Влияние настоя семян свеклы обыкновенной (Beta vulgaris) на показатели белкового и углеводного обмена у животных в подостром и хроническом эксперименте при воздействии ацетата меди
Keywords: copper acetate; heavy metals; creatinine; urea; glucose; Béta vulgáris; seed infusion